2016
DOI: 10.1128/msphere.00086-16
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Recombinant Reoviruses To Display gp41 Membrane-Proximal External-Region Epitopes from HIV-1

Abstract: Vaccines to protect against HIV-1, the causative agent of AIDS, are not approved for use. Antibodies that neutralize genetically diverse strains of HIV-1 bind to discrete regions of the envelope glycoproteins, including the gp41 MPER. We engineered recombinant reoviruses that displayed MPER epitopes in attachment protein σ1 (REO-MPER vectors). The REO-MPER vectors replicated with wild-type efficiency, were genetically stable, and retained native antigenicity. However, we did not detect HIV-1-specific immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…We and others have found that genetic modification of reovirus can improve oncolytic activity in vitro and in animal cancer models (87)(88)(89)(90)(91). Reovirus also provides a potential vaccine vector (92,93). Efficient production of reovirus recombinants will therefore expedite production and testing of genetically modified reovirus for oncolytic and vaccination purposes.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have found that genetic modification of reovirus can improve oncolytic activity in vitro and in animal cancer models (87)(88)(89)(90)(91). Reovirus also provides a potential vaccine vector (92,93). Efficient production of reovirus recombinants will therefore expedite production and testing of genetically modified reovirus for oncolytic and vaccination purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The MPER is a highly conserved region targeted by broadly neutralizing antibodies (bnAbs) [ 100 ]. Although such MPER-specific antibodies have been shown to prevent infection through passive immunization [ 101 , 102 , 103 ], numerous animal studies have failed to elicit robust or sufficiently broad neutralizing antibody responses using a variety of strategies [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Issues hindering the development of gp41 MPER as a vaccine target include poor immunogenicity due in part to steric hindrance and lack of accessibility [ 100 , 115 ], hydrophobicity that renders the MPER prone to aggregation in solution [ 116 ], immunodominance of adjacent gp41 regions lacking any neutralizing epitopes [ 117 , 118 ] and the apparent auto-reactivity of MPER-specific bnAbs towards cell membrane lipids [ 119 , 120 ].…”
Section: Introductionmentioning
confidence: 99%